Perancangan Sistem Informasi Manajemen Administrasi Markas PMI Kota Tangerang (Si Markot) Berbasis Web - Adriyanto, Florensa Gelisa; Hendri Hendri; Farabi, Nur Ali (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The administrative system implemented at the Tangerang City PMI Headquarters is still semi-computerized, causing several issues such as inconsistent document formats, higher risk of recording errors, longer processing times, and excessive paper use. Additionally, delays in determining the leader’s availability often hinder the disposition and signing process, resulting in postponed activities. To address these problems, a Web-Based Administrative Management Information System was developed, named “Si-Markot”. This system aims to improve the efficiency of managing incoming and outgoing correspondence through digital archiving, electronic disposition, and digital signature features for leaders. Si-Markot functions as a structured digital repository that enables quick document searches and real-time tracking. The research methodology includes observation and literature study, with system development based on the Rapid Application Development (RAD) approach. System modeling was conducted using Unified Modeling Language (UML), implemented with PHP programming language and phpMyAdmin as the database. The system was tested using the Black Box Testing method. The results of this study produced a web-based administrative management application specifically designed for managing correspondence at the Tangerang City PMI Headquarters, improving efficiency, reducing paper usage, and accelerating document disposition and processing.